Status and Recent Developments of Pantoea stewartii subsp. stewartii Causes the Wilt Disease in Maize in Indonesia: A Review - Najamuddin, Erwin; Djaya, Ernawati; Djaenuddin, Nurasiah; Muis, Amran; Fauriah, Ria; Salim, Salim (Universitas Sebelas Maret, 2023)
Pantoea stewartii subsp. stewartii is a pathogen that causes Stewart wilt on maize. This disease is important in maize. Infection early in growth can cause yield losses of up to 100%. This review examines the history, recent developments, economic impacts and developments of detection technology of Stewart wilt diseases. This paper was created by reviewing several articles relevant to the purpose of the topic. The article's results revealed that the pathogen underwent many changes, including its name, taxonomy, physiological abilities, status as an important pathogen in many countries and the development of detection technology. Currently, P. stewartii subsp. stewartii belongs to the Erwiniaceae family and has physiological abilities that can be distinguished from bacteria of the same genus and species. This pathogen has been reported to spread to more than 82 countries, including Indonesia, with 18 host plants. Some areas have reported pathogens in Indonesia, but no vector has been written. The biggest economic threat caused by this disease is the industrial production of corn seeds which require strict phytosanitary requirements and are free from pathogens. To anticipate its spread, there are four methods of detection of pathogenic bacteria that are commonly used, but serological and molecular detection technologies are the main recommendations.